Svjetska zdravstvena organizacija u međunarodnom pravu / The World Health Organization in International Law - Borić, Nežla (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
This article represents a critical review of the WHO's (World Health Organization) approach to control of infectious diseases on the international level. It puts focus primarily on the IHR (International Health Regulations) from the standpoint of developing countries, but also globally. Although IHR represent the most important legal instrument that the WHO has adopted until now, they have been heavily criticized—among other things—for their limited scope of application and the fact that the health measures which they lay down are founded on an out-dated understanding of national sovereignty. Therefore, this article sets as its task to evaluate whether the IHR, as proposed by the WHO in 2004, are able to meet the challenges of both new and resurgent pathogens in the globalizing world of today. The author concludes that, notwithstanding its long neglect of international law, the WHO’s policy is gradually shifting towards a regulatory approach to global public health. Though the revised IHR lack procedural details in various areas, they still represent the central legal instrument in the transnational health regime. Regulated public health system is possible only within a global normative framework, which implies cooperation between states, establishing corresponding inter-governmental organizations and supporting their work, along with assigning an active role to the non-governmental actors. The World Health Organization with their International Health Regulations certainly have an important, prominent and leading role in international health law, which has been shown in their engagement during the global pandemic of COVID-19 which has affected the whole world now.